INNOVATIVE BIOTECHNOLOGIES OF PLANT PROTECTION: ACHIEVEMENTS AND PROSPECTS (International Conference on Modern Science and Scientific Studies, 2025)
This article is devoted to innovative biotechnology of plant protection, analyzing recent achievements and future prospects. Modern methods such as genetic engineering, biological control, RNA interference and nano-biotechnologies are of great importance in protecting plants from pests, diseases and climate change.